Evaluation of The Implementation of Inclusive PAUD at preschool Lentera Insan Kindergarten Depok - Nofrianto, Robby; Priyanti, Nita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Inclusive education is an approach that provides opportunities for all children, including children with special needs (ABK), to receive equal education services. Lentera Insan Kindergarten Depok is one of the PAUD or preschool institutions that has implemented an inclusive education system since 2002. This study aims to evaluate the implementation of inclusive education at Lentera Insan Kindergarten, especially in the curriculum, assessment, and learning of children with special needs at Lentera Insan Kindergarten. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that Lentera Insan Kindergarten has an inclusive student admission system that considers initial assessments by expert psychologists, therapists and accompanying teachers. Learning planning is carried out through an Individual Learning Program (PPI) which is prepared based on the child's needs by involving psychologists. The implementation of the inclusive program is supported by special accompanying teachers, as well as an inclusion-based learning approach. Evaluation of inclusive education is carried out periodically through child development assessments and coordination with supporting staff.